2023
DOI: 10.1111/exd.14771
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deficiency anaemia comorbidity in generalized pustular psoriasis hospitalizations

Abstract: Generalized pustular psoriasis (GPP) is a rare heterogeneous cutaneous disease characterized by multiple flares of painful pustules with widespread inflammation. 1 Chronic systemic inflammation in GPP may result in anaemia by mechanisms such as iron sequestration in macrophages. 2 Lee et al. 3 demonstrated an increased risk of psoriasis in chronic kidney disease patients with low haemoglobin levels. Though some level of associations between anaemia and GPP has been previously considered, we sought to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Because of the extensive systemic inflammation of GPP and the low incidences of severe comorbidities in our cohort, it is reasonable to speculate that this is anaemia of inflammation caused by prolonged immune activation. 27,28 In addition, as inflammation and severity markers of psoriasis, 21,22 the differences of NLR and PLR support the conclusion that GPP represents a severer disease.…”
Section: Discussionmentioning
confidence: 67%
“…Because of the extensive systemic inflammation of GPP and the low incidences of severe comorbidities in our cohort, it is reasonable to speculate that this is anaemia of inflammation caused by prolonged immune activation. 27,28 In addition, as inflammation and severity markers of psoriasis, 21,22 the differences of NLR and PLR support the conclusion that GPP represents a severer disease.…”
Section: Discussionmentioning
confidence: 67%
“…The strengths of this SLR are its robust and thorough methodology, which followed Cochrane's methodological expectations, namely independent screening of eligible studies and quality assurance of all data extracted, and its up‐to‐date and comprehensive searches. In contrast to the recently published narrative review exploring the HRQoL in people with GPP, 44 multiple databases were systematically searched using comprehensive search terms. In addition to the limitations of the studies as described above, there are a few limitations of the SLR that may affect the generalisability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings add to the results from a recent narrative review also sought to determine the HRQoL in people with GPP. 44 The review, which identified 12 studies via a PubMed keyword search, also concluded that while there is a paucity of studies, the existing evidence shows that people with GPP experience a substantial impact on their HRQoL. Overall, further studies, perhaps recruiting people with GPP globally with the help of patient advocacy groups, with a larger population and extensive clinical data might allow for more robust data on the impact of the severity of the flares, as well as looking at differences in HRQoL during and between flares and in relation to other possible confounding factors, namely gender, age and socio-economic status.…”
Section: Investigating the Hrqol And Severity Of Symptoms In People W...mentioning
confidence: 99%
“…Understanding the extracutaneous manifestations of GPP can guide clinicians in providing comprehensive care to patients and managing potential comorbidities effectively. The impact of comorbidities on GPP is further emphasized by Patel S et al, who demonstrated increased costs of care and longer hospital stays among GPP patients with associated deficiency anaemias 6 . Case series and reports included in this special issue highlight the diverse clinical phenotypes of GPP and underscore the importance of individualized care.…”
mentioning
confidence: 95%
“…The impact of GPP on patients' quality of life (QoL) was also addressed in this issue. Patel PM et al highlight the large impact of GPP on patients' lives, emphasizing the need for routine assessment of QoL in individuals affected by the condition 12 . Zimmermann et al examine the socioeconomic impact of GPP on patients, healthcare systems and society as a whole, emphasizing the importance of increased awareness, improved access to care and targeted support systems 13 .…”
mentioning
confidence: 99%